Wasting Away with Cirrhosis: A Review of Hepatic Sarcopenia - Jan Freeman; Andrew Austin; Ernesto Robalino Gonzaga (Journal of Renal and Hepatic Disorders, 2019)
The complications of decompensated cirrhosis are well documented and include variceal bleeding, fluid retention, and hepatic encephalopathy. A less well recognized complication of cirrhosis is muscle wasting or sarcopenia. It is now recognized to have a significant impact on patient survival, especially in patients who are awaiting liver transplantation. An understanding of the pathophysiology of muscle protein homeostasis has led to several proposed mechanisms of sarcopenia and the potential to reverse muscle loss. This review discusses the potential mechanisms of sarcopenia and highlights the possible future means of reversing sarcopenia.